Long term gluten consumption in adults without celiac disease and risk of coronary heart disease: prospective cohort study. (2nd May 2017) - Lebwohl, Benjamin; Cao, Yin; Zong, Geng; Hu, Frank B; Green, Peter H R; Neugut, Alfred I; Rimm, Eric B; Sampson, Laura; Dougherty, Lauren W; Giovannucci, Edward; Willett, Walter C; Sun, Qi; et al.
Abstract : Objective  To examine the association of long term intake of gluten with the development of incident coronary heart disease. Design  Prospective cohort study. Setting and participants  64 714 women in the Nurses' Health Study and 45 303 men in the Health Professionals Follow-up Study without a history of coronary heart disease who completed a 131 item semiquantitative food frequency questionnaire in 1986 that was updated every four years through 2010. Exposure  Consumption of gluten, estimated from food frequency questionnaires. Main outcome measure  Development of coronary heart disease (fatal or non-fatal myocardial infarction). Results  During 26 years of follow-up encompassing 2 273 931 person years, 2431 women and 4098 men developed coronary heart disease. Compared with participants in the lowest fifth of gluten intake, who had a coronary heart disease incidence rate of 352 per 100 000 person years, those in the highest fifth had a rate of 277 events per 100 000 person years, leading to an unadjusted rate difference of 75 (95% confidence interval 51 to 98) fewer cases of coronary heart disease per 100 000 person years. After adjustment for known risk factors, participants in the highest fifth of estimated gluten intake had a multivariable hazard ratio for coronary heart disease of 0.95 (95% confidence interval 0.88 to 1.02; P for trend=0.29). After additional adjustment for intake of whole grains (leaving the remaining variance of gluten corresponding to refined grains), the multivariate hazard ratio was 1.00 (0.92 to 1.09; P for trend=0.77). In contrast, after additional adjustment for intake of refined grains (leaving the variance of gluten intake correlating with whole grain intake), estimated gluten consumption was associated with a lower risk of coronary heart disease (multivariate hazard ratio 0.85, 0.77 to 0.93; P for trend=0.002). Conclusion  Long term dietary intake of gluten was not associated with risk of coronary heart disease. However, the avoidance of gluten may result in reduced consumption of beneficial whole grains, which may affect cardiovascular risk. The promotion of gluten-free diets among people without celiac disease should not be encouraged.